First International Electronic Conference on Nutrients, Microbiota and Chronic Disease 2020
DOI: 10.3390/iecn2020-06985
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative and Apoptotic Induction Effect of Elateriospermum Extract on Human Lung Cancer Cell Line A549

Abstract: Natural products derived from plants are used to treat cancer due to fewer side effects compared to standard treatments available for cancer. The second highest cancer that causes death worldwide is lung cancer. Therefore, this study aimed to determine the cytotoxic activity of hot and cold aqueous extract of E. tapos seed and shell on human cancer cell line A549 as well as the apoptosis mechanism. The apoptosis mechanisms were evaluated by cell viability (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The second most potent compound was Cd(L)Cl 2 derivative with IC 50 = 0.052 mg/mL. These results showed that new compounds had significant cytotoxic effects on A549 cell line, especially since they are comparable with one of the most important cytotoxic compounds: cisplatin (IC 50 = 0.017 ± 0.0001 mg/mL) [ 40 ]. Similar results were obtained by other research teams [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 96%
“…The second most potent compound was Cd(L)Cl 2 derivative with IC 50 = 0.052 mg/mL. These results showed that new compounds had significant cytotoxic effects on A549 cell line, especially since they are comparable with one of the most important cytotoxic compounds: cisplatin (IC 50 = 0.017 ± 0.0001 mg/mL) [ 40 ]. Similar results were obtained by other research teams [ 41 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 96%